Formation of a C–C double bond from two aliphatic carbons. Multiple C–H activations in an iridium pincer complex1. Issue 3 (16th March 2015) - Polukeev, Alexey V.; Marcos, Rocío; Ahlquist, Mårten S. G.; Wendt, Ola F.
<x xml:space="preserve">Abstract</x> Iridium can mediate a reversible intramolecular coupling reaction involving up to four unactivated Csp3–H bonds, to give a carbon–carbon double bond.